Pride in language teaching: Scale development and associations with work engagement, wellbeing, and burnout - Khajavy, Gholam Hassan; Smid, Dávid; Mercer , Sarah; Murillo-Miranda , Carlos; Mairitsch , Astrid; Sulis , Giulia; Shin, Sun; Mairi , Salam (Studies in Second Language Learning and Teaching, 2026)
In recent years, there has been a growing interest in research on language teacher emotions while relatively fewer studies have focused on language teachers’ professional pride. This study aims to develop and validate a scale for language teacher pride (LTP), and it seeks to understand how this critically important emotion may be linked to other central, conceptually related constructs including wellbeing, work engagement, and burnout. Data were collected employing an online questionnaire in which 423 language teachers from 52 countries took part in the study. The results of exploratory factor analysis, confirmatory factor analysis, and exploratory structural equation modeling revealed that the newly constructed Language Teacher Pride Scale (LTPS) reflects the multifaceted nature of LTP as a positive emotional experience. We further found that language teachers with a heightened sense of pride in their teaching were more engaged in their work, had higher wellbeing, and were less prone to burnout. We hope that the results of this study will aid future research by informing policy and practice as well as theory building about the role of pride as a potential core construct in positive psychology, which can help us to understand and support teacher flourishing.